Implementation of Interactive Video Content H5P to Increase Student Activeness in Receiving Praktik Plumbing Material - Iriandy; Ayu Saputri Bahar; Andi Khaerun Niza; Fitry Purnamasari; Andi Muh Akbar Saputra (Information Technology Education Journal, 2025)
This study aims to improve student activeness and understanding in learning praktik plumbing through the application of interactive learning videos based on LUMI H5P. The method used is ADDIE model-based development which includes the stages of analysis, design, development, implementation, and evaluation. The interactive video was developed to support independent learning by inserting evaluation questions in the video material. The results show that the use of interactive content based on H5P can increase student learning motivation, accelerate task completion, and facilitate the evaluation process with automatic feedback. The implementation of this technology is also able to overcome the limitations of static document-based learning. In conclusion, the use of LUMI H5P in learning praktik plumbing significantly improves student engagement and understanding, and promotes more flexible and effective learning. It is recommended that the use of H5P interactive content be integrated more widely in various practical courses to support the quality of digital learning.